2015
DOI: 10.1097/hcr.0000000000000117
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory Muscle Training in Pulmonary Arterial Hypertension

Abstract: Inspiratory muscle training promotes significant improvements in respiratory muscle strength and functional capacity, thus resulting in a reduction of dyspnea during activities of daily living and less fatigue in PAH patients. Inspiratory muscle training is a clinically practical treatment for PAH without any complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 40 publications
4
63
1
7
Order By: Relevance
“…Strengthening the respiratory muscles has been reported to improve exercise tolerance, QOL and reduce symptoms in patients with COPD, HF and PAH. In 2015, Saglam et al . implemented isolated respiratory muscle training (RMT) in PAH ( n = 14 intervention and n = 15 sham).…”
Section: Pulmonary Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strengthening the respiratory muscles has been reported to improve exercise tolerance, QOL and reduce symptoms in patients with COPD, HF and PAH. In 2015, Saglam et al . implemented isolated respiratory muscle training (RMT) in PAH ( n = 14 intervention and n = 15 sham).…”
Section: Pulmonary Factorsmentioning
confidence: 99%
“…Strengthening the respiratory muscles has been reported to improve exercise tolerance, QOL and reduce symptoms in patients with COPD, HF and PAH. In 2015, Saglam et al 82 implemented isolated respiratory muscle training (RMT) in PAH (n = 14 intervention and n = 15 sham). They reported increases in inspiratory muscle strength and an average improvement of 50 m in walking distance after a 6-week inspiratory muscle training programme.…”
Section: Respiratory Muscle Dysfunctionmentioning
confidence: 99%
“…In a study conducted by Adamopoulos et al, to improve pulmonary ventilation, combined AT/IMT led to significant improvements in dyspnea and QoL in HF patients compared to AT alone (Adamopoulos et al, 2014). Studies conducted on HF (Saglam et al, 2015) and other chronic diseases have shown that IMT reduces dyspnea during routine activities (Karadallı et al, 2016) by improving the functional and maximal exercise capacity (Saglam et al, 2015) .…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21]27,[29][30][31][32][33] The improvements in 6MWD were less, compared to the inpatient protocol ( Fig. [18][19][20][21]27,[29][30][31][32][33] The improvements in 6MWD were less, compared to the inpatient protocol ( Fig.…”
Section: Frequency Duration and Intensity Of Exercisementioning
confidence: 98%